2020
DOI: 10.1103/physreva.101.032309
|View full text |Cite
|
Sign up to set email alerts
|

Conditional probability distributions of finite absorbing quantum walks

Abstract: Quantum walks are known to have nontrivial interactions with absorbing boundaries. In particular it has been shown that an absorbing boundary in the one dimensional quantum walk partially reflects information, as observed by absorption probability computations. In this paper, we shift our sights from the local phenomena of absorption probabilities to the global behavior of finite absorbing quantum walks in one dimension. We conduct our analysis by approximating the eigenbasis of the associated absorbing quantu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Here we used the fact, well known from linear algebra, that the left and right eigenvalues are equal; hence they are denoted with ξ. These are complex numbers, and for the problem at hand, it was shown that these eigenvalues are all on the unit disk |ξ| ≤ 1 [60,61]. We will use normalized states…”
Section: The Survival Operatormentioning
confidence: 99%
“…Here we used the fact, well known from linear algebra, that the left and right eigenvalues are equal; hence they are denoted with ξ. These are complex numbers, and for the problem at hand, it was shown that these eigenvalues are all on the unit disk |ξ| ≤ 1 [60,61]. We will use normalized states…”
Section: The Survival Operatormentioning
confidence: 99%
“…We can notice that once a quantum walker penetrates into the interior, the situation for this quantum walker is the same as that of the absorption problem of quantum walks [14]. The detailed analysis on the absorption problem especially the spectral analysis can be seen, for example, [15]. Then, for a convergence time to the stationary state, such a spectral analysis on the truncated finite matrix of the time evolution operator of our model, which is non-unitary, will be useful.…”
Section: Where Is the Comfortable Place For Quantum Walkers On The Pa...mentioning
confidence: 97%
“…Note that since this quantum walk can be converted to a quantum walk with absorption walls, the problem is reduced to analysis on a finite matrix E M , which is obtained by picking up from the total unitary time evolution operator with respect to the perturbed region Γ M . See [16] for a precise spectral results on E M . This paper is organized as follows.…”
Section: Introductionmentioning
confidence: 99%